A heart of wisdom : religion and human wholeness - Friedman, Maurice S. (Albany, NY : State University of New York Press, 1992)
Annotation Describes religion not as an external creed and form, or as a subjective inspiration, but as a conscious and immediate meeting with ultimate reality. Religion, then, becomes involved with the wholeness of human life; truth appears in the particular and unique as well as in the universal; and duality promotes a separation between spirit and life that neither can survive. Oriented towards Judaism and Christianity. Paper edition (unseen), $16.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Religion and Literature -- Solitude and Community -- PART FOUR: The Tension Between Past and Present -- Peter Pan's Shadow: Tradition and Modernity -- The Dialectic Between Spirit and Form -- The Paradox of Religious Leadership -- PART FIVE: Religion and Human Wholeness -- Spontaneity, Decision, and Personal Wholeness -- Religion and Ethics: ""The Way to Do Is to Be"" -- World View and Existential Trust -- Is Religion the Enemy of Humankind? -- Back Matter -- Notes -- INDEX -- Back Cover.
Includes bibliographical references (pages 231-240) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Religion; Religions; Religion; Religions; religion (discipline); religions (belief systems, cultures); RELIGION -- Comparative Religion; RELIGION -- Reference; Religions; Religion; Religion; Religions